The skin crawls, the stomach turns: ectoparasites and pathogens elicit distinct defensive responses in humans. Issue 1955 (28th July 2021) - Kupfer, Tom R.; Fessler, Daniel M. T.; Wu, Bozhi; Hwang, Tiffany; Sparks, Adam Maxwell; Alas, Sonia; Samore, Theodore; Lal, Vedika; Sakhamuru, Tanvi P.; Holbrook, Colin
Abstract : Disgust has long been viewed as a primary motivator of defensive responses to threats posed by both microscopic pathogens and macroscopic ectoparasites. Although disgust can defend effectively against pathogens encountered through ingestion or incidental contact, it offers limited protection against ectoparasites, which actively pursue a host and attach to its surface. Humans might, therefore, possess a distinct ectoparasite defence system—including cutaneous sensory mechanisms and grooming behaviours—functionally suited to guard the body's surface. In two US studies and one in China, participants ( N = 1079) viewed a range of ectoparasite- and pathogen-relevant video stimuli and reported their feelings, physiological sensations, and behavioural motivations. Participants reported more surface-guarding responses towards ectoparasite stimuli than towards pathogen stimuli, and more ingestion/contamination-reduction responses towards pathogen stimuli than towards ectoparasite stimuli. Like other species, humans appear to possess evolved psychobehavioural ectoparasite defence mechanisms that are distinct from pathogen defence mechanisms.